Commentary: Response to commentary by Rutter on Munafo et al. (2014). (6th August 2014) - Munafò, Marcus R.; Zammit, Stanley; Flint, Jonathan
<x xml:space="preserve">Abstract</x> Rutter's commentary (Rutter, 2014) on our article (Munafò et al., 2014) provides us the opportunity to clarify some issues that he (and therefore, we suspect, others) may have misunderstood.